First record of leafhopper genus Satsumanus Ishihara from India (Hemiptera: Cicadellidae: Deltocephalinae) with description of a new species - Rajgopal, N. N.; Stuti; Ningombam, Arati; Langlentombi, Leishangthem Chanu (Zootaxa, 2023)
The leafhopper genus Satsumanus Ishihara of tribe Opsiini is newly reported from India based on a new species, Satsumanus chajingensis Rajgopal & Stuti sp. nov. (Manipur: Imphal West), here described and illustrated. Materials are deposited in the National Pusa Collection, Division of Entomology, ICAR-Indian Agricultural Research Institute (IARI), New Delhi, India. Photographic illustrations, a species checklist, key to species of the genus and distribution map are provided.